Politeness in e-mails of Arab students in Malaysia - Zena Moayad Najeeb,; Marlyna Maros,; Nor Fariza Mohd Nor, (Penerbit UKM, 2012)
This study analyzes the politeness strategies found in Arab postgraduate students’ e-mails to their supervisors during their period of study at Malaysian universities. Many studies have revealed that language ability, social adjustment and culture shock are the most challenging issues that are frequently encountered by the international students. Arab students who are studying in Malaysia, likewise, encounter challenges as they experience different cultures in their new environment, and in their efforts at learning English in an academic environment. Politeness tends to have various implications in cross-cultural communication. This research used quantitative and qualitative approaches to analyze eighteen e-mails that were sent by six Arab postgraduate students to their supervisors.The politeness strategies were analyzed according to Brown and Levinson’s (1987)politeness theory, and the degrees of directness were categorized according to Cross Cultural Speech Act Realization Pattern (CCSARP) Blum-Kulka and Olshtain (1984)coding scheme. The findings show that Arab students used various politeness strategies, including the use of positive and negative politeness strategies. They tended to be more direct in their requests via e-mail when communicating in English. No student used the indirect strategy. This study provides an insight into the Arab students’ politeness strategies that would help to avoid misunderstanding, and misinterpretation of their emails,as well as to improve student’s pragmatic awareness in writing e-mails in English.